Lung Protective Ventilation Adherence and Outcomes for Patients With COVID-19 Acute Respiratory Distress Syndrome Treated in an Intermediate Care Unit Repurposed to ICU Level of Care - Chad H. Hochberg, MD, MHS; Aaron S. Case, MD, MHS; Kevin J. Psoter, PhD; Daniel Brodie, MD; Rebecca H. Dezube, MD; Sarina K. Sahetya, MD, MHS; Carrie Outten, RN, MSN; Lara Street, RN, MSN; Michelle N. Eakin, PhD; David N. Hager, MD, PhD (Critical Care Explorations, 2024)
OBJECTIVE:. During the COVID-19 pandemic, some centers converted intermediate care units (IMCUs) to COVID-19 ICUs (IMCU/ICUs). In this study, we compared adherence to lung protective ventilation (LPV) and outcomes for patients with COVID-19-related acute respiratory distress syndrome (ARDS) treated in an IMCU/ICU versus preexisting medical ICUs (MICUs). DESIGN:. Retrospective observational study using electronic medical record data. SETTING:. Two academic medical centers from March 2020 to September 2020 (period 1) and October 2020 to May 2021 (period 2), which capture the first two COVID-19 surges in this health system. PATIENTS:. Adults with COVID-19 receiving invasive mechanical ventilation who met ARDS oxygenation criteria (Pao2/Fio2 ≤ 300 mm Hg or Spo2/Fio2 ≤ 315). INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. We defined LPV adherence as the percent of the first 48 hours of mechanical ventilation that met a restrictive definition of LPV of, tidal volume/predicted body weight (Vt/PBW) less than or equal to 6.5 mL/kg and plateau pressure (Pplat) less than or equal to 30 cm H2o. In an expanded definition, we added that if Pplat is greater than 30 cm H2o, Vt/PBW had to be less than 6.0 mL/kg. Using the restricted definition, period 1 adherence was lower among 133 IMCU/ICU versus 199 MICU patients (92% [95% CI, 50–100] vs. 100% [86–100], p = 0.05). Period 2 adherence was similar between groups (100% [75–100] vs. 95% CI [65–100], p = 0.68). A similar pattern was observed using the expanded definition. For the full study period, the adjusted hazard of death at 90 days was lower in IMCU/ICU versus MICU patients (hazard ratio [HR] 0.73 [95% CI, 0.55–0.99]), whereas ventilator liberation by day 28 was similar between groups (adjusted subdistribution HR 1.09 [95% CI, 0.85–1.39]). CONCLUSIONS:. In patients with COVID-19 ARDS treated in an IMCU/ICU, LPV adherence was similar to, and observed survival better than those treated in preexisting MICUs. With adequate resources, protocols, and staffing, IMCUs provide an effective source of additional ICU capacity for patients with acute respiratory failure.